Autoimmunity in Pulmonary Arterial Hypertension: Evidence for Local Immunoglobulin Production - Shu, Ting; Xing, Yanjiang; Wang, Jing (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary arterial hypertension (PAH) is a progressive life-threatening disease. The notion that autoimmunity is associated with PAH is widely recognized by the observations that patients with connective tissue diseases or virus infections are more susceptible to PAH. However, growing evidence supports that the patients with idiopathic PAH (IPAH) with no autoimmune diseases also have auto-antibodies. Anti-inflammatory therapy shows less help in decreasing auto-antibodies, therefore, elucidating the process of immunoglobulin production is in great need. Maladaptive immune response in lung tissues is considered implicating in the local auto-antibodies production in patients with IPAH. In this review, we will discuss the specific cell types involved in the lung in situ immune response, the potential auto-antigens, and the contribution of local immunoglobulin production in PAH development, providing a theoretical basis for drug development and precise treatment in patients with PAH.